Potential of Aframomum melegueta and Xylopia aethiopica Against Taenia spp.: Plant-Based Remedies as Novel Anthelmintics - Fekandine V. Douti; Gnatoulma Katawa; Kathrin Arndts; Fagdéba D. Bara; Essimanam R. Awesso; Simplice D. Karou; Achim Hoerauf; Manuel Ritter (Pharmaceuticals)
Background/Objectives: Taeniasis, a zoonotic infection, is a common foodborne disease. Niclosamide and praziquantel have proven to be effective in treating it, but the use of the same drugs can lead to resistance, so alternative drugs need to be explored. This study investigated the anthelmintic potential of derived fractions from hydroethanolic extracts (HEs) of Aframomum melegueta (AM) and Xylopia aethiopica (XA), two medicinal plants known for their diverse bioactive properties. Methods: AM-HE fractions (dichloromethane fraction (DCMF), ether fraction (EF), aqueous fraction (AF)) and XA-HE fractions (chloroform fraction (CF), ether fraction (EF), and aqueous fraction (AF)) were used, and in vitro anthelmintic activity was assessed against Taenia spp. by using an adult motility assay for the worm’s paralysis time determination. The parasiticidal and parasitostatic activity was also tested on Taenia spp. adult worms. Cell viability was further evaluated using propidium iodide (PI) staining, with albendazole (20 mg/mL) as the reference drug. Results: The three fractions of each plant exhibited significant, dose-dependent anthelmintic activity, with AM-HE and XA-CF showing the greatest effects at 20 mg/mL. AM-EF demonstrated significant activity at 0.4% and 0.8%. Irreversibility tests revealed that most of the treated worms remained paralysis, except those exposed to the AF of both plants. PI staining confirmed the dose-dependent mortality of Taenia cells treated with HE, DCMF, and AF of AM. Conclusions: These results underscore the potential of AM and XA extracts and fractions as alternative treatments for helminth infections. Further, in vivo studies are warranted to confirm their safety and therapeutic efficacy.